Penerapan Tahapan Membangun Aplikasi Knowledge Management pada Subdivisi Orafin di PT X - Kurniali, Sartika (Bina Nusantara University, 2012)
The application of knowledge management on the Internet keeps growing. This is due to the Internet that offers new opportunities to use the knowledge assets, define the type of new knowledge assets, and spread even outside the organization. The emerging social media is enabling internet-based knowledge sharing system. Social media itself is nothing new, but now has undergone many changes that allow for much interactive interaction and much greater number of users. The results showed that knowledge management and social media contain almost the same components. This allows the role of social media on the application of knowledge management, such as collaboration tools accompanied by a clear business purpose.